Neurologic morbidity and functional independence in adult survivors of childhood cancer - Stefanie C. Vuotto; Mingjuan Wang; M. Fatih Okcu; Daniel C. Bowers; Nicole J. Ullrich; Kirsten K. Ness; Chenghong Li; Deo Kumar Srivastava; Rebecca M. Howell; Todd M. Gibson; Wendy M. Leisenring; Kevin C. Oeffinger; et al. (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective To examine associations between neurologic late effects and attainment of independence in adult survivors of childhood cancer treated with central nervous system (CNS)‐directed therapies. Methods A total of 7881 survivors treated with cranial radiation therapy (n = 4051; CRT) and/or intrathecal methotrexate (n = 4193; IT MTX) ([CNS‐treated]; median age [range] = 25.5 years [18–48]; time since diagnosis = 17.7 years [6.8–30.2]) and 8039 without CNS‐directed therapy reported neurologic conditions including stroke, seizure, neurosensory deficits, focal neurologic dysfunction, and migraines/severe headaches. Functional independence was assessed using latent class analysis with multiple indicators (independent living, assistance with routine and personal care needs, ability to work/attend school, attainment of driver's license, marital/partner status). Multivariable regression models, adjusted for age, sex, race/ethnicity, and chronic health conditions, estimated odds ratios (OR) or relative risks (RR) for associations between neurologic morbidity, functional independence, and emotional distress. Results Among CNS‐treated survivors, three classes of independence were identified: (1) moderately independent, never married, and non‐independent living (78.7%); (2) moderately independent, unable to drive (15.6%); and (3) non‐independent (5.7%). In contrast to 50% of non‐CNS‐treated survivors and 60% of siblings, a fourth fully independent class of CNS‐treated survivors was not identified. History of stroke (OR = 2.50, 95% CI: 1.70–3.68), seizure (OR = 9.70, 95% CI: 7.37–12.8), neurosensory deficits (OR = 2.67, 95% CI: 2.16–3.31), and focal neurologic dysfunction (OR = 3.05, 95% CI: 2.40–3.88) were associated with non‐independence among CNS‐treated survivors. Non‐independence was associated with emotional distress symptoms. Interpretation CNS‐treated survivors do not attain full independence comparable to non‐CNS‐treated survivors or siblings. Interventions to promote independence may be beneficial for survivors with treatment‐related neurological sequalae.